The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/tesj.420
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaposing William and Graciela: Exploring gender nonconformity through drama‐based pedagogy in a dual‐language classroom

Abstract: Using multicultural children's books La Asombrosa Graciela and William's Doll as springboards for discussion surrounding gender roles, this study examines the role of drama‐based pedagogy in the developing understanding of gender roles in a second‐grade Spanish dual‐language classroom. This practitioner inquiry shows students’ responses to the disruption of traditional understandings of gender roles and gender nonconformity portrayed in those books as they rehearsed creative alternatives to resolve the main ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Examples of cisgenderism could be found in representation in children's literature where cisgender identities are preferred, valued, and accepted while teachers are hesitant to make curricular changes due to institutional, social, and internal influences (Meyer, 2008). However, a recent case study (Caldas, 2018) has explored how to incorporate gender nonconformity through drama‐based pedagogy in dual‐language classrooms where second‐grade children were reported to demonstrate positivity and powerful allyship. When heteronormative assumptions and cisgenderism are not questioned and challenged in the classroom, those who do not belong to the norms, such as LGBTQ+, will continue facing (hetero)sexual harassment, homophobic harassment, transphobic remarks, and other discriminatory actions (Caldas, 2018; Meyer, 2008; Trevor Project, n.d.).…”
Section: What Are Common Heteronormative Assumptions and Cisgenderism?mentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of cisgenderism could be found in representation in children's literature where cisgender identities are preferred, valued, and accepted while teachers are hesitant to make curricular changes due to institutional, social, and internal influences (Meyer, 2008). However, a recent case study (Caldas, 2018) has explored how to incorporate gender nonconformity through drama‐based pedagogy in dual‐language classrooms where second‐grade children were reported to demonstrate positivity and powerful allyship. When heteronormative assumptions and cisgenderism are not questioned and challenged in the classroom, those who do not belong to the norms, such as LGBTQ+, will continue facing (hetero)sexual harassment, homophobic harassment, transphobic remarks, and other discriminatory actions (Caldas, 2018; Meyer, 2008; Trevor Project, n.d.).…”
Section: What Are Common Heteronormative Assumptions and Cisgenderism?mentioning
confidence: 99%
“…However, a recent case study (Caldas, 2018) has explored how to incorporate gender nonconformity through drama‐based pedagogy in dual‐language classrooms where second‐grade children were reported to demonstrate positivity and powerful allyship. When heteronormative assumptions and cisgenderism are not questioned and challenged in the classroom, those who do not belong to the norms, such as LGBTQ+, will continue facing (hetero)sexual harassment, homophobic harassment, transphobic remarks, and other discriminatory actions (Caldas, 2018; Meyer, 2008; Trevor Project, n.d.).…”
Section: What Are Common Heteronormative Assumptions and Cisgenderism?mentioning
confidence: 99%
See 1 more Smart Citation
“…Trinh (2022) describes the importance of recognizing queer experiences for all students, and especially for queer students with limited or interrupted formal education, so that school does not become a location of further marginalization and exclusion. Additionally, Caldas (2018) found that drama‐based practices can provide language learners with opportunities to challenge traditional gender roles through portraying gender‐nonconforming characters. By requiring students to select a woman from history, the assignment—and school environment more broadly—assumed all students shared this gender identity, and it did not provide opportunities for students to perform as historical figures who might challenge gender binaries.…”
Section: Structural Considerations: Narrative Elements Established By...mentioning
confidence: 99%